Clinical Evaluation of Pathological Changes in the Area of ​​Dental Implants Affected by Peri-Implantitis - Izay М. Е. (Actual Dentistry, 2026)
The occurrence of peri-implantitis is influenced by several risk factors, the combined effects of which compromise the prognosis of the function of the established intraosseous support, thereby affecting the outcome of the patient’s prosthetic rehabilitation. Existing methods of treating peri-implantitis do not incorporate a preventive component, which involves periodic screening using clinical and additional methods to assess the condition of the dental implant and the oral cavity as a whole. The aim is to determine the prevalence and etiological risk factors for peri-implant complications, specifically peri-implantitis, as a function of the prosthetic structures used, the duration of function, and patient age. Materials and methods of the study. The main group comprised 493 patients from the University Dental Clinic LLC, Uzhhorod (211 men (42.8%) and 282 women (57.2%)), and the control group comprised 326 individuals without any pathological changes in the area of the installed intraosseous supports. Patient age was categorized in 10-year intervals; the exclusion criterion was prosthetic function for more than 10 years. To assess changes in the dental status of patients with peri-implantitis, indicators of plaque index, bleeding on probing, probing depth, and bone loss were compared with those of patients in the control group. Numerical data processing was performed using the adapted Microsoft Excel 2019, with the XLSTAT and Analyse It plugins and utilities. Results. Among the risk factors that most significantly determined the possibility of developing peri-implantitis, the following should be highlighted: the presence of periodontal lesions in history—HR = 4.52 (95% CI 2.7546–8.4768), the presence of periodontal lesions at the time of examination—HR = 4.94 (95% CI 2.9375–8.8467), inadequate level of oral hygiene—HR = 4.23 (95% CI 2.2352–8.4366), non-compliance with the protocol of control examinations—HR = 3.61 (95% CI 1.9463–6.0468), the level of bone crest reduction after 1 year of functioning of more than 2 mm—HR = 3.96 (95% CI 2.6746–5.3756). Conclusions. The prevalence of peri-implant complications in the form of peri-implantitis was 12.64% of the total number of implants. Among the risk factors for the development of peri-implant lesions with the most pronounced level of prognostic impact are the presence of periodontal lesions in the anamnesis and at the time of examination, inadequate level of oral hygiene, non-compliance with the protocol of control examinations, the level of bone crest reduction after 1 year of operation of more than 2 mm, and the fact of functioning of implants as supports for removable dentures.